2017
DOI: 10.1039/c7nr01037k
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nitrogen functionalities in enhancing the excitation-independent green-color photoluminescence of graphene oxide dots

Abstract: Fluorescent graphene oxide dots (GODs) are environmentally friendly and biocompatible materials for photoluminescence (PL) applications. In this study, we employed annealing and hydrothermal ammonia treatments at 500 and 140 °C, respectively, to introduce nitrogen functionalities into GODs for enhancing their green-color PL emissions. The hydrothermal treatment preferentially produces pyridinic and amino groups, whereas the annealing treatment produces pyrrolic and amide groups. The hydrothermally treated GODs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…To verify that ROS were involved in the PDT effect of the amino-N-GQDs, we used α-tocopherol for ROS neutralization. 13 This step reduced the quantity of the generated ROS, and we discovered an increase in cell viability, as expected. Inadvertent exposure of the amino-N-GQDs to white light would have led to the production of 1 O 2 and O 2 .…”
Section: Identification Of the Generated Rossupporting
confidence: 81%
See 2 more Smart Citations
“…To verify that ROS were involved in the PDT effect of the amino-N-GQDs, we used α-tocopherol for ROS neutralization. 13 This step reduced the quantity of the generated ROS, and we discovered an increase in cell viability, as expected. Inadvertent exposure of the amino-N-GQDs to white light would have led to the production of 1 O 2 and O 2 .…”
Section: Identification Of the Generated Rossupporting
confidence: 81%
“…Moreover, the values observed for the amino-N-GQDs are consistent with those reported in the literature (0.340-0.403 nm). 12,13 The XRD results also indicated that the basal plane was not considerably functionalized. This finding is in agreement with the theories that graphene has considerably more active edges than in-plane carbons do and that functional groups are present at the amino-N-GQD edges.…”
Section: Characterization Of Gqd-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the nitrogen incorporation leads to substantial changes in the electronic properties of the CDs 38 43 . Similar effects were also seen in graphene oxide-based dots 44 , 45 . In particular, graphitic N atoms have a strong n-doping effect due to the additional π ∗ electrons, while pyridinic and pyrrolic N atoms have a weak p-doping character 46 .…”
Section: Introductionsupporting
confidence: 69%
“…Graphene oxide was prepared from a natural graphite powder (Bay carbon Inc., Bay City, MI, USA) using a modified Hummers' method [10,[37][38][39][40]. Graphite (8.5 M) and NaNO 3 (0.6 M) (Merck & Co., Kenilworth, NJ, USA) were mixed with H 2 SO 4 (FUJIFILM Wako Chemicals USA Inc., Richmond, VA, USA).…”
Section: Preparation Of Amino-n-gqdsmentioning
confidence: 99%